Comparison of Honey With Alcohol as a Fixative in Fine Needle Aspiration Cytology - Ishaq, Ruqqayya; Azmat, Henna; Omair, Maria; Sheikh, Ahmareen Khalid; Tanwani, Ashok Kumar (International Journal of Pathology, 2018)
Fine Needle Aspiration Cytology (FNAC) is a useful diagnostic aid in benign and malignant lesions. The diagnostic accuracy of FNAC depends on the sampling technique, fixative used, quality of staining and of course the meticulosity of interpretation by the pathologist. The widely used fixative in this procedure is 95 % Alcohol which although readily available, has a number of limitations for use. It is expensive and hence subject to pilferage. Also, it is a volatile liquid with an irritant smell and is said to be carcinogenic. Recent attempts have been made to prove that honey is also a comparable fixative for cytological specimens. It is a natural organic product, odourless and not known to cause any disease. Secondly it is relatively cheaper and not prone to be mishandled, making it an efficient contender for use as a fixative. In this study, we analyzed and compared the efficacy of cytological smears fixed in 95% alcohol and 20% honey solution. The results of our study showed no statistical significant difference in the fixative properties of honey and alcohol. Our results, therefore, confirmed that honey can safely be used as an alternate to alcohol in cytology specimens